2023
DOI: 10.3389/feduc.2023.1197396
|View full text |Cite
|
Sign up to set email alerts
|

Gains from the transition from face-to-face to digital/online modality to improve education in emergency

Abstract: Education during emergencies demands attention from both institutions and governments, as the incidence of disasters and crises continues to increase worldwide due to various challenges that threaten humanity, including climate change, terrorism, food and water scarcity, energy crises, poverty, and inequality. Emergency remote teaching (ERT) is a critical factor in providing academic opportunities, building resilience, and promoting recovery for affected individuals. This research examines the challenges assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Other relevant terms were "capture" (0.005), "attention" (0.003), "feedback" (0.003), and "interaction" (0.002). In agreement with Camacho-Zuñiga et al (2023), it can be inferred that capturing students' attention, providing truly efficient feedback, and, in general, lecturing without the usual immediate and physical bidirectional communication of a face-to-face course were significant challenges for the professors.…”
Section: Faculty Members' Strengths and Weaknessessupporting
confidence: 56%
See 1 more Smart Citation
“…Other relevant terms were "capture" (0.005), "attention" (0.003), "feedback" (0.003), and "interaction" (0.002). In agreement with Camacho-Zuñiga et al (2023), it can be inferred that capturing students' attention, providing truly efficient feedback, and, in general, lecturing without the usual immediate and physical bidirectional communication of a face-to-face course were significant challenges for the professors.…”
Section: Faculty Members' Strengths and Weaknessessupporting
confidence: 56%
“…]. This also highlights a unique opportunity for HEIs to improve, since in previous studies innovation was identified as inherent to online educational models (Camacho-Zuñiga et al, 2023).…”
Section: Investigating the Relationships Between Competencesmentioning
confidence: 80%
“…Despite the vast sources of online learning, unreliable sources lead to misinformation and a diminished quality of education. For DE, fairness and efficacy of assessment still represent a challenge (Camacho-Zuñiga et al, 2023), particularly with the broader use of generative artificial intelligence. DE tools do not always fulfill a Universal Instructional Design adding barriers to students with disabilities.…”
Section: Limitationsmentioning
confidence: 99%